Assessing of aloe vera for antimicrobial against infected capsicum annuum by colletotrichumcapsici for anthracnose disease and bacillus subtilis - Ong, Yee Fen (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Nowadays, overuse of chemical fungicide has side effect which is harmful to human consumption, causes environmental problem, and destroy the antagonist microorganisms. Overuse of antibiotic also resulted to multi drug-resistant (MDR), where antibiotics become ineffective against the bacterial strains. Therefore, it is important to develop natural fungicide and bactericide from plant extract. For the current study, chilli anthracnose fungus, Colletotrichum capsici and bacteria Bacillus subtilis were used for antifungal and antibacterial activity. C. capcisi was isolated from chilli and its morphology was identified by its greyish-white colony colour, fluffy cottony look on PDA, rings of acervuli and curved conidia. Antifungal activity was demonstrated by using different concentration Aloe vera extract (1000ppm to 5000 ppm). Aloe vera has low inhibition against C. capsici at every concentration which were 1.17 % at 1000 ppm and 7.20 % at 5000ppm. As for the antibacterial activity, different concentrations of Aloe vera extracts (1.25 mg/ml until 200 mg/ml) were tested on B. subtilis by using disc diffusion method. Aloe vera has high inhibition against B. subtilis at 200 mg/ml which was 21.33 mm while there is no inhibition zone at 1.25 mg/ml.B. subtilis proved that MIC value is 2.5 mg/ml. The phytochemical test confirmed the presence of terpenoids, flavonoids, tannins and steroids. In conclusion, Aloe vera can be biological fungicide to replace chemical fungicide against C. capsici but research still need to carry out to enhance the efficiency towards C.capsici. On the other hand, Aloe vera is suitable to be commercialized as natural bactericide.